2009
DOI: 10.3354/dao02050
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus VP37 interacts with VP28 and VP26

Abstract: White spot syndrome virus (WSSV) is one of the most virulent pathogens affecting penaeid shrimp, causing high mortality in infected populations. Interactions between virus structural proteins are likely to be important for virus assembly. Many steps of the WSSV assembly and maturation pathway remain unclear. In the present study, the interaction between VP37 and envelope or nucleocapsid proteins was characterized. VP37 was expressed in Escherichia coli and confirmed by Western blotting. Pure WSSV virions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Such homologous genes have been found in WSSV VP28, VP26 and VP24 [11], and further studies demonstrated that VP24 interacts with VP28 and is involved in virus infection [15]. We have reported that VP37 interacts with VP28 and VP26 [8]. Until now, there is little information concerning the role of VP292.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Such homologous genes have been found in WSSV VP28, VP26 and VP24 [11], and further studies demonstrated that VP24 interacts with VP28 and is involved in virus infection [15]. We have reported that VP37 interacts with VP28 and VP26 [8]. Until now, there is little information concerning the role of VP292.…”
Section: Discussionmentioning
confidence: 94%
“…The other procedures were the same as above. Recombinant VP28 was constructed as previously reported [8].…”
Section: Wssv Envelop and Nucleocapsid Protein Preparedmentioning
confidence: 99%
See 2 more Smart Citations
“…Since VP24 is a major viral protein and also interacts with other structural proteins, it has been speculated that groups of these proteins form a basic frame work for the virus upon which the other proteins build up [18]. Liu et al [27] attempted to study the morphology of WSSV by interaction study. The overlay assay and the subsequent His-pull down assay confirmed the interaction of VP37 with VP26 and VP28.…”
Section: Protein Interaction Studies With White Spot Syndrome Virus (mentioning
confidence: 99%